The complete vegetarian cookbook : a fresh guide to eating well with 700 foolproof recipes (America's Test Kitchen, 2015)
This vegetarian cookbook from the editors at America's Test Kitchen features 250 vegan and 500 gluten-free recipes. Each recipe is listed and identified as vegan, gluten-free or fast (less than 45 minutes from start to finish).